2002
DOI: 10.1086/338877
|View full text |Cite
|
Sign up to set email alerts
|

Far Ultraviolet Spectroscopic ExplorerObservations of Possible Infalling Planetesimals in the 51 Ophiuchi Circumstellar Disk

Abstract: We present the first observations of the circumstellar (CS) disk system 51 Ophiuchi with the Far Ultraviolet Spectroscopic Explorer. We detect several absorption lines arising from the unusual metastable atomic species N I ( 2 D), N I ( 2 P ), and S II ( 2 D). These levels lie 1.8 -3.6 eV above the ground level and have radiative decay lifetimes of 2 days or less, indicating that the lines arise from warm CS gas. The high S/N FUSE spectra, obtained six days apart, also show time-variable absorption features ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 20 publications
4
30
1
Order By: Relevance
“…Contrary to β Pic, large amount of molecular gas (CO, CO 2 , H 2 O and NO) has been seen around 51 Oph by the Short-Wavelength-Spectrometer on board the Infrared Space Observatory (ISO) (van den Ancker et al 2001). A controversy remains about the quantity of CO. Absorption lines by CO in the Far-Ultraviolet were not detected by FUSE (Roberge et al 2002). Nevertheless, all studies suggest that the circumstellar matter is most likely in the form of a Keplerian disk rather than in a spherical shell.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Contrary to β Pic, large amount of molecular gas (CO, CO 2 , H 2 O and NO) has been seen around 51 Oph by the Short-Wavelength-Spectrometer on board the Infrared Space Observatory (ISO) (van den Ancker et al 2001). A controversy remains about the quantity of CO. Absorption lines by CO in the Far-Ultraviolet were not detected by FUSE (Roberge et al 2002). Nevertheless, all studies suggest that the circumstellar matter is most likely in the form of a Keplerian disk rather than in a spherical shell.…”
Section: Introductionmentioning
confidence: 87%
“…The UV and optical part of the SED are well fitted by a Kurucz model and show no excess testifying that the accretion of matter onto the star is low (Waters et al 1988;Malfait et al 1998). However, infalling ionic and atomic gases were observed which prompted Grady et al (1991) to claim that 51 Oph is in the same evolutionary state as β Pic (see also Roberge et al 2002). Contrary to β Pic, large amount of molecular gas (CO, CO 2 , H 2 O and NO) has been seen around 51 Oph by the Short-Wavelength-Spectrometer on board the Infrared Space Observatory (ISO) (van den Ancker et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In order to search for possible variability they degraded their observations to a resolving power of R = 100 000 (i.e., half the resolution of our spectra presented in this paper), enabling them to compare them to data obtained by Lagrange-Henri et al (1990). The analysis of Crawford et al (1997) does not show evidence for spectral variability in Ca K, while Roberge et al (2002) report the detection of timevariable N, N, O, and Fe lines from FUSE observations in their recent study of HR 6519. Moreover, HR 6519 shows clear evidence for the presence of circumstellar gas from the detection of the Fe line at 4583.84 Å (Dunkin et al 1997) which is not observed in the interstellar medium since it arises from a metastable level 2.8 eV above the ground state.…”
Section: Hr 5367 (ψ Cen)mentioning
confidence: 96%
“…Certainly, the advantage of using high resolution spectropolarimeters such as ESPaDOnS at the Canada-France-Hawaii Bernacca & Perinotto (1970), c Grady et al (1996), d van den Ancker et al (1998), e Acke & Waelkens (2004), f Hamidouche et al (2008), g this work, h Dunkin et al (1997), i Hubrig et al (2007b), j Alencar et al (2003), k Royer et al (2007), l Mora et al (2001), m Slettebak (1982), n de la Reza & Pinzón (2004), o Beskrovnaya et al (2004), p Alecian et al (2008), q Landstreet et al (2008) Pontoppidan et al (2007b), aa Siebenmorgen et al (2000), bb Kessler-Silacci et al (2005), cc Okamoto et al (2004), dd Schütz et al (2005b), ee Dommanget & Nys (1994), f f Baines et al (2006), gg Corporon & Lagrange (1999), hh Stelzer et al (2006), ii Chen et al (2006a), j j Augereau et al (2001), kk Carmona et al (2007), ll Stecklum et al (1995), mm Reipurth & Zinnecker (1993), nn Roberge et al (2002), oo Grady et al (2007), pp Stauffer et al (1995), qq SIMBAD, rr Eisner et al (2004), ss Grady et al (2004), tt Pirzkal et al (1997), uu Schnerr et al (2007), vv Blondel et al (2006), ww van den Ancker et al (1997), xx Wade et al (2007), yy …”
Section: Observations and Data Reductionmentioning
confidence: 99%